Selegen - a computer program for genetic selection in the breeding of perennial species - Resende, Marcos Deon Vilela de; Oliveira, Edilson Batista de (Pesquisa Agropecuaria Brasileira, 1997)
"Selegen" software was developed to help tree breeding programs of forest species, but it can also be used in breeding programs of other perennial or semi-perennial species and animal where selection of individuals is more important than selection of groups of individuals. Selegen runs under IBM/PC-DOS and is based on algorithms which maximize efficiency of selection by comparing different selection methods in terms of accuracy, genetic gain, effective size of population, and genetic gain variables for each specific experimental situation. This paper presents aspects which should be considered in methods for selection of individuals and all analysis which can be made by the program.